(3efgLjI GdHMK GdYdejs - (3NVjQ cGXe(B, (3MehOs; (3GddhRj ehSi SdGeI(B, s ((3YeGf(B:s (3GKQGA ddfTQ h GdJhRjY(B,s, 2008)
(3jJfGhd gPG GdcJGH GdeMGhQ GdJGdjI ebOeI aj GdHMK GdYdej , GdJMQj GdYdej , eJZjQGJ GdHMK GdYdej hGdGWGQ GdfXQj , GdJMdjd GdGMUGFj ddHMK ,CSGdjH LeY GdHjGfGJ , NWhGJ GdHMK GdYdej , GdGWGQ GdYGe ddHMK , YQV GdHjGfGJ hJMdjdgG , fJGFL GdHMK hGdJhUjGJs
(3HjHdjhZQGajG U(B.293s
Keywords: (3HMK Ydejs; (3WQb GdHMKs; (3efgLjIs